La contaminación atmosférica como problema multidimensional: aporte de las universidades peruanas durante el periodo 2001-2020 - Murriel Gonzales, Federico Augusto (2025)
Air pollution is addressed in Peru with regulations focused only on its physical dimension, even though it also presents a social dimension and a political dimension. The knowledge contributed by Peruvian universities can be leveraged to design regulations that address this problem with a multidimensional approach; however, its current status is unknown. This work goes beyond a literature review as it aims to answer the research question: What knowledge have Peruvian universities contributed on the physical, social, and political dimensions of air pollution at the national level during the period 2001- 2020? For this purpose, the concepts of the physical, social, and political dimensions of air pollution were used as the theoretical framework, and the state-of-the-art technique as the methodology. Knowledge on air pollution from 84 academic articles from academic journals of 23 Peruvian universities was collected and analyzed. The results indicate that the knowledge provided by Peruvian universities is insufficient to support regulations with a multidimensional approach. Additionally, they reveal gaps in knowledge and show trends followed by these institutions in the last two decades, such as the prevalence of positivism as the main paradigm in knowledge generation.